PENGARUH ATRIBUT DEWAN TERHADAP NILAI PERUSAHAAN - Golda Belladonna Umbing; Ade Yuniati; Rosel Rosel; Natasya Angelica; Dan Arga Perkasa; Theo Joshua Nathaniel (Jurnal Ekonomi Integra, 2022)
This research examines the impact of board size, number of board meetings, age of board members, independent members on board of commissioners, woman on board, foreign board members, board’s education background, political connection, and military experience on firm value. This research was a quantitative study with hypothesis testing approach. This research used 165 observations from manufacturing companies listed on Indonesia Stock Exchange period 2017-2019 as sample. Data collection method was indirect in form of archived data. Data analysis used multiple regression analysis. This research finds that size of board directors and foreign directors positively affect firm value. Size of board commissioners and military experience on board members negatively affects on firm value.  On the contrary, other variables show no effect on firm value. Some of the variables in this research were not significant, thus future research could conduct tests using different proxies. There might be another factor that has more significant effect on firm value, which is not analyzed in this study. This research contributes to the development of literature on board attributes by identifying board characteristics toward firm value.